The Effect of Work Environment and Compensation on Hospital Nurses’ Performance at the Inpatient Unit - Benny Prakarsa Yustianto; Toni Prasetia; Nanda Pramana Putra; Ahmad Sopyan; Suharto Suharto (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study aimed to examine the effects of environmental support and compensation on nurses’ work performance at Bintang Amin Hospital in Lampung. The study was motivated by the growing demand for high-quality nursing services and the need to identify organizational factors that improve nurses’ performance in inpatient care settings. Research Methodology: A quantitative, cross-sectional design was used in this study. It involved 60 nurses working in inpatient units, selected using simple random sampling. Data were collected using structured questionnaires that measured environmental support, compensation, and nurses’ work performance. Data analysis included validity and reliability tests, as well as hypothesis testing using multiple regression. Results: Environmental support has a positive and significant effect on nurses’ work performance. Supportive working conditions, teamwork, and supervisory support contribute to higher performance. Compensation also has a positive and significant influence, indicating that fair remuneration enhances nurses’ motivation and work commitment. Environmental support and compensation significantly affect nurses’ work performance. Conclusions: Nurses’ work performance was strongly influenced by organizational factors, particularly environmental support and compensation. Hospitals that provide supportive work environments and fair compensation systems tend to achieve better nursing performance and service quality. Limitations: This study was limited to a single hospital and used a cross-sectional design, limiting generalizability and failing to capture changes over time. Other factors affecting nurses’ performance were not examined. Contributions: This study contributes empirical evidence to the nursing and healthcare human resource management literature by demonstrating the combined effects of environmental support and compensation on nurses’ work performance in an Indonesian hospital.